The correlates of religion and state: an introduction. Issue 1 (1st January 2019) - Fox, Jonathan
ABSTRACT: This volume examines the Religion and State Round 3 (RAS3) dataset which includes information of State Religion Policy (SRP) for 183 countries and self-governing territories between 1990 and 2014. This collection includes a general discussion of the dataset but most of the contributions take these data and use them to analyse the intersections between SRP and a wide range of phenomena including civil wars, terrorism, international conflict, attitudes towards religion and state, constitutional promises of religious freedom, and religious mobilisation. While this volume constitutes the formal primary presentation and analysis of the RAS3 dataset, it is intended to be the beginning of an ongoing discussion.